2015
DOI: 10.1146/annurev-physiol-021014-071846
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel β Subunits: Emerging Targets in Channelopathies

Abstract: Voltage-gated sodium channels (VGSCs) are responsible for initiation and propagation of action potentials in excitable cells. VGSCs in mammalian brain are heterotrimeric complexes of α and β subunits. Originally called “auxiliary,” we now know that β subunit proteins are multifunctional signaling molecules that play roles in both excitable and non-excitable cell types, and with or without the pore-forming α subunit present. β subunits function in VGSC and potassium channel modulation, cell adhesion, and gene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
255
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(272 citation statements)
references
References 158 publications
(269 reference statements)
5
255
0
2
Order By: Relevance
“…A recent review drew attention to the possible pharmacological manipulation of b subunits of Na + channels rather than the pore-forming a subunits (O'Malley and Isom, 2015). This approach may be especially attractive as three different types of b subunits are differentially and selectively expressed in small, medium, and large DRG neurons (Zhao et al, 2011;Ho et al, 2012).…”
Section: Role Of Ectopic Activity In Primary Afferent Fibersmentioning
confidence: 99%
“…A recent review drew attention to the possible pharmacological manipulation of b subunits of Na + channels rather than the pore-forming a subunits (O'Malley and Isom, 2015). This approach may be especially attractive as three different types of b subunits are differentially and selectively expressed in small, medium, and large DRG neurons (Zhao et al, 2011;Ho et al, 2012).…”
Section: Role Of Ectopic Activity In Primary Afferent Fibersmentioning
confidence: 99%
“…2B) (Ahern et al, 2016). The biophysical properties of alpha subunits, as well as their trafficking, are regulated by the interacting VGSC beta subunits, which comprise 4 genes and 5 members, as one of them presents two splicing variants (O'Malley and Isom, 2015). Among the latter, the predominant beta subunit expressed in pancreatic beta cells is Scn1b (Ernst et al, 2009;Zhang et al, 2014).…”
Section: Ion Channel Modulation In Beta Cellsmentioning
confidence: 99%
“…Also, the β subunits are expressed in various cell/tissue types, including heart, skeletal muscle, PNS, CNS, adrenal gland and kidney (50). It has been reported that mutations in β subunits are associated with several diseases, such as epilepsy, cardiac arrhythmia, and sudden death syndromes (51). The VGSC β subunits serve as therapeutic targets, therefore, development of selective drugs targeting these accessory subunits would be beneficial.…”
Section: Voltage-gated Sodium Channelmentioning
confidence: 99%